2013 International Conference on Biometrics and Kansei Engineering 2013
DOI: 10.1109/icbake.2013.49
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Barrel Distortion and Super-Resolution for Single-View-Based Ear Biometrics Rotated in Depth

Abstract: To improve the viability of the authors' previous work regarding single-view-based ear biometrics, empirical evaluations were performed using super-resolution images and images with barrel distortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Moreover, super‐resolution techniques might be of particular interest in case video footage is available. These methods could be employed in order to reduce compression artefacts and hence improve the robustness and biometric performance of an ear recognition system [41]. Further, feature fusion approaches [9, 11, 72] could be utilised to bridge the observed performance gap between systems operating on raw and highly compressed images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, super‐resolution techniques might be of particular interest in case video footage is available. These methods could be employed in order to reduce compression artefacts and hence improve the robustness and biometric performance of an ear recognition system [41]. Further, feature fusion approaches [9, 11, 72] could be utilised to bridge the observed performance gap between systems operating on raw and highly compressed images.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that while conventional detection algorithms appear rather robust in presence of these signal degradations, recognition algorithms are highly influenced by noise causing a significant decrease in accuracy for images exhibiting peak signal to noise ratio (PSNR) values of 20-30 dB. Further, effects of barrel distortion and super-resolution on ear biometrics are investigated in [41]. It has been empirically shown that biometric performance drops in case of barrel distorted images, which might be compensated by the use of super-resolution images for model normal vector creation.…”
Section: Iet Biometricsmentioning
confidence: 99%
“…In research on biometric authentication technology, authentication methods using moving images of the pinna, the external part of the ear in humans and other mammals, have been studied [1]. Several studies have concluded that the shape of the pinna is complex and differs significantly across individuals [2][3][4][5]. Conventional studies indicate the feasibility of an authentication system using the acoustic transfer functions of the pinna and the ear canal [6].…”
Section: Introductionmentioning
confidence: 99%